2003
DOI: 10.1124/jpet.103.052316
|View full text |Cite
|
Sign up to set email alerts
|

The Orally Available Spleen Tyrosine Kinase Inhibitor 2-[7-(3,4-Dimethoxyphenyl)-imidazo[1,2-c]pyrimidin-5-ylamino]nicotinamide Dihydrochloride (BAY 61-3606) Blocks Antigen-Induced Airway Inflammation in Rodents

Abstract: Spleen tyrosine kinase (Syk) tyrosine kinase plays essential roles in receptors for Fc portion of immunoglobulins and B cell receptor complex signaling in various inflammatory cells; therefore, inhibitors of Syk kinase may show potential as antiasthmatic/allergic therapeutics. We identified 2-[7-(3,4-dimethoxyphenyl)-imidazo[1,2-c]pyrimidin-5-ylamino]-nicotinamide dihydrochloride (BAY 61-3606), a potent (K i ϭ 7.5 nM) and selective inhibitor of Syk kinase. BAY 61-3606 inhibited not only degranulation (IC 50 va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
134
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(142 citation statements)
references
References 32 publications
6
134
1
1
Order By: Relevance
“…BAY61-3606 was selected over other Syk inhibitors because it has been shown previously to inhibit Syk activity in vivo in rodents (54,55). We observed that BAY61-3606 significantly reduces brain A␤ 38 , A␤ 40 , and A␤ 42 levels in Tg PS1/ APPsw mice (Fig.…”
Section: In Vivo Effects Of the Selective Syk Inhibitor Bay61-3606 Onmentioning
confidence: 79%
“…BAY61-3606 was selected over other Syk inhibitors because it has been shown previously to inhibit Syk activity in vivo in rodents (54,55). We observed that BAY61-3606 significantly reduces brain A␤ 38 , A␤ 40 , and A␤ 42 levels in Tg PS1/ APPsw mice (Fig.…”
Section: In Vivo Effects Of the Selective Syk Inhibitor Bay61-3606 Onmentioning
confidence: 79%
“…Importantly, BAY 61-3606 is very selective for Syk at the concentrations used (68). We first assessed the effects of Syk inhibition on DENV-2 replication by measuring intracellular DENV E-protein expression in ADE-inoculated monocytes at 24 hpi (Fig.…”
Section: Ade-induced Syk Activation Is Dispensable For Denvmentioning
confidence: 99%
“…R112 is another Syk inhibitor formulated for intranasal use [39] and has a rapid effect and quickly inhibits mast cell activation. Additional Syk inhibitors with less specificity include piceatannol and BAY 61-3606 [40,41]. …”
Section: Syk Inhibition Therapy In Autoimmune and Allergic Inflammmentioning
confidence: 99%
“…Alternatively, targeting the intracellular signaling cascade may represent an attractive approach. Appropriately, protein tyrosine kinases such as Syk, Lyn, and Btk have been directly implicated in IgE-dependent mast cell activation and have been suggested as targets for therapeutic intervention [39-41]. Syk represents the most attractive target because studies with mast cells derived from Syk-deficient indicated mice showed that Syk is important in the activation of mediators of degranulation, eicosanoid, and cytokine production [23,39].…”
Section: Syk Inhibition Therapy In Autoimmune and Allergic Inflammmentioning
confidence: 99%
See 1 more Smart Citation